Computer-Based Vectorcardiograph for Research Purposes - Vozda, M.; Hrvolova, B.; Krohova, J.; Smondrk, M.; Penhaker, M. (Elektronika ir Elektrotechnika, 2013)
The vectorcardiography (VCG) represents the cardiac electric field by vectors and provides a better morphological interpretation of the cardiac electrical field. The main objective of this paper has been to describe our VCG device that has been determined for scientific research and for the clinical diagnosis of heart diseases. We have designed the hardware as a small portable device and the software that measures data saved in a raw form accessible for further processing. The main contribution is in the new way of common mode reduction (driven right leg circuit). The designed device has a great potential thanks to the new methods of interpretation and automatic signal evaluation an also thanks to the small procurement price. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5650